Research on teaching portuguese as a second language for foreigners. Investigación sobre la enseñanza del portugués como segunda lengua para extranjeros - Rodrigues, Mateus Gabilanes (2021)
The objective of this work was to investigate, through a review of the state of knowledge type, the process of teaching and learning the Portuguese language to foreigners in Brazil. It is a qualitative, descriptive and analytical research. Academic publications dealing specifically with the subject were analyzed in the databases: Scientific Electronic Library Online (SciELO); Educational Resources Information Center (ERIC) and Brazilian Digital Library of Theses and Dissertations (BDTD), between 2005 and 2018, checking trends and references on the subject, through bibliographic review. It was possible to value and subsidize other types of studies with the same research interest. Through the works found, an in-depth analysis was carried out. Preliminary readings of popular science texts revealed the importance attributed to knowledge of culture in the teaching of a given language to these speakers. As a conclusion, the need for further studies on the subject is identified, due to the importance it has for the future of Brazilian education and its impacts.